PEMBUATAN EDIBLE FILM DARI PATI TEMU HITAM (Curcuma aeruginosa Roxb.) DENGAN PENAMBAHAN GLISEROL - Mhd Iqbal Nusa; Syakir Naim Siregar; Laila Muzdalifah (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2017)
The research objectives determine the effect of concentration Wild Ginger starch in suspension and adding glycerol on the edible film making of wild ginger starch.  The Factorial Complete Randomized design was used with two factors. The first factor as treatments were  the number of concentration Wild Ginger Starch in suspension (T) at four levels namely T1=2%, T2 = 4%, T3 = 6%, T4 = 8%.  The second factor as treatment was the number of concentration glycerol adding (G) at four levels namely G1 = 20%, G2 = 30%, G3 = 40%, G4 = 50%. The physical characteristics  film were observed as Parameters namely The film thickness, percentage elongatios of film, and Water Vapor Transmission Rate (WVTR). The statistical analysis of the parameters indicated that increasing concentrations of  wild ginger starch in suspensions  very significantly difference effect (P<0,01) for film thickness,  percentage elongation of film, and Water Vapor Transmission Rate (WVTR). The increasing of glycerol adding very significantly difference effect (P<0,01) for film thickness, and percentage elongation of film. Unlike the Water Vapor Transmission Rate (WVTR) was significantly difference effect (P<0,05). Treatment interactions gave a very significantly different effect (P<0,01) for the thickness, and percentage  elongation of  film. Unsignificantly difference effect (P>0,05) for Water Vapor Transmission Rate (WVTR).Keywords: Wild ginger starch, glycerol, WVTR, edible film.